(untitled) (LEGAL DIALOGICA, 2025)
This study aims to determine and analyze the application of restorative justice in resolving traffic accidents that cause death and to determine and analyze the factors that influence the application of restorative justice in resolving traffic accidents that cause death. This study is an empirical legal research method. Based on the description of the application of restorative justice in traffic accidents that cause death, it has been applied, but not all traffic accidents that cause death can be carried out. Restorative justice can only be carried out if it meets the elements, and criminal acts against human life and factors that influence the application of restorative justice in resolving traffic accidents that cause death, namely law enforcement factors, legal substance factors and legal culture factors. Research recommendations in this case require investigators to increase socialization to the community regarding what criminal acts can be applied to restorative justice in handling the settlement of traffic accident cases that cause death. Cooperation is needed between the government, law enforcement officers, and the community to create a legal system that is more adaptive, just, and able to resolve cases in a more humane and restorative manner. Abstrak: Penelitian ini bertujuan untuk mengetahui dan menganalisis penerapan restorative justice dalam penyelesaian kecelakaan lalu lintas yang menyebabkan meninggalnya orang dan untuk mengetahui dan menganalisis faktor-faktor yang mempengaruhi penerapan restorative justice dalam penyelesaian kecelakaan lalu lintas yang menyebabkan meninggalnya orang. Penelitian ini adalah metode penelitian hukum empiris. Berdasarkan uraian penerapan restorative justice dalam kecelakaan lalu lintas yang menyebabkan meninggalnya orang sudah diterapkan akan tetapi tidak semua kecelakaan lalu lintas yang menyebabkan meninggalnya orang dapat dilakukan restorative justice hanya bisa dilakukan jika memenuhi unsur, dan tindak pidana terhadap nyawa orang dan Faktor yang mempengaruhi penerapan restorative justice dalam penyelesaian kecelakaan lalu lintas yang mengakibatkan meninggalnya orang yaitu Faktor penegak hukum, faktor substansi hukum dan faktor budaya hukum. Rekomendasi penelitian dalam hal ini perlu kiranya penyidik untuk meningkatkan sosialisasi kepada masyarakat terkait dengan tindak pidana apa saja yang dapat diterapkan restorative justice dalam penanganan penyelesaian perkara tindak pidana kecelakaan lalu lintas yang menyebabkan meninggalnya orang. Dibutuhkan kerjasama antara pemerintah, aparat penegak hukum, dan masyarakat untuk menciptakan sistem hukum yang lebih adaptif, berkeadilan, dan mampu menyelesaikan kasus dengan yang lebih manusiawi dan restoratif.